Providing innovation incentives for the green transition - Armin Schmutzler (University of Zurich, Department of Economics, 2025)
By affecting prices and thereby market shares of green and brown firms, product innovations and process innovations influence industry emissions even when they do not directly affect the emission intensity of the innovating firm. Using a differentiated two-stage duopoly, this paper therefore analyzes the effects of environmental policy on such innovations, and it asks how these effects differ from each other and from those of environmental innovations that directly reduce the emission intensity. The paper investigates the determinants of R&D investments, showing in particular that incentives for certain types of potentially beneficial innovations may be negative. Moreover, it analyzes how suitable policies can foster green innovation.
Keywords: Q55; L13; 330; Innovation; Environmental Policy; Imperfect Competition